Encyclopedia of the Reformed faith - Benedetto, Robert, 1950-; Calian, Carnegie Samuel; Cochrane, Arthur C; Crocco, Stephen D; Gamble, Richard C; Gerstner, John H. (John Henry), 1914-1996; McKim, LindaJo H; Miller, Donald G. (Donald George), 1909-1997; Partee, Charles; Purves, Andrew, 1946-; Rogers, Jack, 1934-2016; Smith, Elwyn A. (Elwyn Allen), 1919-; et al. (Louisville, Ky. Westminster/John Knox Press ; Edinburgh Saint Andrew Press, 1992)
More than two hundred international scholars from a variety of denominations contribute to this outstanding, one-volume reference book. Comprehensive in scope, it stresses the importance of events, persons, and theological concepts that have been significant to the Reformed tradition
Contributors include: R. Benedetto, C.S. Calian, A.C. Cochrane, S.D. Crocco, R.C. Gamble, J.H. Gerstner, L.H. McKim, D.G. Miller, C. Partee, A. Purves, J.B. Rogers, E.A. Smith, J.E. Wilson, and M.L. Wolfe
Keywords: Dogmatic Theology (3GddGghJ GdYbjOjs; Reformed Church -- Encyclopedias; Presbyterian Church -- Faith